2021
DOI: 10.3390/toxins13110759
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and Comparative Inhibitory Efficacy of Naturally Occurring Compounds on Vegetative Growth and Deoxynivalenol Biosynthesis in Fusarium culmorum

Abstract: The fungal pathogen Fusarium culmorum causes Fusarium head blight in cereals, resulting in yield loss and contamination of the grain by type B trichothecene mycotoxins such as deoxynivalenol (DON), and its acetylated derivatives. Synthesis of trichothecenes is driven by a trichodiene synthase (TRI5) that converts farnesyl pyrophosphate (FPP) to trichodiene. In this work, 15 naturally occurring compounds that belong to the structural phenol and hydroxylated biphenyl classes were tested in vitro and in planta (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…For instance, Siranidou et al [223] reported a synergistic antifungal effect of p-coumaric with ferulic acid in reducing the mycelial growth of F. culmorum. An equimolar combination of propyl gallate and thymol tested at a final concentration of 0.25 mM proved a strong inhibitor of trichothecenes both in vitro and in plants [224]. Oufensou et al [166] tested an equimolar solution of thymol and magnolol, which had an additive effect on F. graminearum, possibly due to the different mode of action of the two compounds, or/and to the ability of one compound of the mixture to cross the fungal membrane, thereby improving the delivery of the other compound.…”
Section: Effect Of the Combination Of Phenolic Compounds With Other Natural Products Or Conventional Fungicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Siranidou et al [223] reported a synergistic antifungal effect of p-coumaric with ferulic acid in reducing the mycelial growth of F. culmorum. An equimolar combination of propyl gallate and thymol tested at a final concentration of 0.25 mM proved a strong inhibitor of trichothecenes both in vitro and in plants [224]. Oufensou et al [166] tested an equimolar solution of thymol and magnolol, which had an additive effect on F. graminearum, possibly due to the different mode of action of the two compounds, or/and to the ability of one compound of the mixture to cross the fungal membrane, thereby improving the delivery of the other compound.…”
Section: Effect Of the Combination Of Phenolic Compounds With Other Natural Products Or Conventional Fungicidesmentioning
confidence: 99%
“…Another computational study on TRI5 protein has been recently carried out by Oufensou et al [224]. A set of 15 naturally occurring compounds belonging to cinnamic acids, gallic esters, terpenes, phenylpropanoids, and 1 phenylethanone was selected for docking onto TRI5.…”
Section: Structure-activity Interactionsmentioning
confidence: 99%
“…In wheat, Fusarium head blight caused by F. culmorum or F. graminearum infection starts from the grain head exterior and passes into the interior. Accordingly, DON is mostly identified in the chaff and the kernel outer layers [ 115 , 116 ]. Grain dusts could have high DON concentrations and other mycotoxins in unsafe levels, which may not be the same in kernels.…”
Section: Mycotoxins: Their Toxicological Mechanisms and Associated He...mentioning
confidence: 99%
“…DON has direct toxicity through its epoxide moiety and consequently requires no metabolic activation for exerting its biological effect. Low-level exposure to trichothecene in animals modulates the expression of several chemokines and cytokines, which are key immune function regulators [ 116 , 117 ]. DON exposure results in upregulating mRNAs responsible for producing chemokines, cytokines, and other proteins associated with the immune system, which can also cause gene transcription.…”
Section: Mycotoxins: Their Toxicological Mechanisms and Associated He...mentioning
confidence: 99%
See 1 more Smart Citation